Microbial community dynamics analysis by high-throughput sequencing in chilled beef longissimus steaks packaged under modified atmospheres. (July 2018) - Yang, Xiaoyin; Zhu, Lixian; Zhang, Yimin; Liang, Rongrong; Luo, Xin
Abstract: The microbial community dynamics were investigated in this study to understand the spoilage of beef steaks packaged in both modified atmosphere packaging (MAP): 80%O2 -MAP (80% O2 /20% CO2 ) and CO-MAP (0.4% CO/30% CO2 /69.6% N2 ). Steaks were stored at 2 °C for 20 days. Meat physicochemical changes and microbial counts were monitored, and the microbial communities were evaluated by high throughput-sequencing. The microbial diversity for both MAP decreased over time and it was more complex in CO-MAP steaks than that in 80%O2 -MAP steaks. B. thermosphacta and Pseudomonas spp. were dominant bacteria of 80%O2 -MAP steaks but Pseudomonas spp. gradually outcompeted the former from day 10. Leuconostoc, Lactobacillus, Lactococcus, Vagococcus and Serratia dominated alternately in CO-MAP steaks during storage, and Lactococcus eventually became the most common bacteria. Predicted metagenomes indicated a higher microbial amino acid and lipid metabolism level in 80%O2 -MAP compared with CO-MAP at day 20, which may contribute to the dramatic physicochemical deterioration of 80%O2 -MAP steaks. Highlights: Bacterial succession in CO-MAP steaks was more complex than for 80%O2 -MAP steaks. Pseudomonas gradually outcompeted B. thermosphacta in 80%O2 -MAP from day 10. Lactococcus were the predominant bacteria by the end of storage in CO-MAP steaks. High microbial amino acid and lipid metabolism in 80%O2 -MAP caused beef spoilage.